Особенности инвестиционных проектов в ядерной энергетике (Путеводитель предпринимателя)
The role of nuclear energy in the fuel and energy complex of Russia is examined, the current state and development trends are analyzed, the main directions of investment activity in the field of nuclear energy technologies are presents and characteristics of investment projects are described.